Extreme skeletal muscle loss during induction chemotherapy is an independent predictor of poor survival in advanced epithelial ovarian cancer patients. Issue 12 (4th October 2020) - Yoshino, Yasunori; Taguchi, Ayumi; Nakajima, Yujiro; Takao, Maki; Kashiyama, Tomoko; Furusawa, Akiko; Kino, Nao; Yasugi, Toshiharu
Abstract: Aim: Skeletal muscle loss is often observed in advanced cancer patients. This study investigates whether skeletal muscle loss is associated with survival outcomes of advanced epithelial ovarian cancer (EOC) patients after induction chemotherapy (IC) in a Japanese cohort. Whether serum inflammatory markers are associated with skeletal muscle changes is also addressed. Methods: We retrospectively reviewed 60 patients with stage III/IV EOC who underwent IC between 2010 and 2017. Skeletal muscle area (SMA) was measured at the third lumbar vertebrae level on a single axial computed tomography‐scan image. Receiver operating curve analysis was used to determine cut‐off values of pre‐ and post‐IC SMA and SMA ratio (SMAR). Univariate and multivariate analyses of overall survival (OS) were conducted using the log–rank test and Cox proportional hazards regression model, respectively. Results: The SMA decreased significantly after IC ( P = 0.019). The cut‐off value between low and high SMAR was 0.96. High or low SMAR was observed in 34 (57%) and 26 (43%) patients, respectively. Univariate analysis revealed that low SMAR was associated with poor OS ( P = 0.025). Multivariate analysis showed that incomplete resection during interval debulking surgery (hazard ratio, 0.30; 95% CI, 0.11–0.80; P = 0.016) and a low SMAR (hazard ratio, 3.17; 95% CI, 1.18–9.06; P = 0.022) were independent predictors of poor OS. Of the serum inflammatory markers investigated, only post‐IC absolute neutrophil count correlated significantly with SMAR ( P = 0.012). Conclusion: Low SMAR can be used to predict poor prognosis in advanced EOC patients who have undergone IC.